EGFR endocytosis is a novel therapeutic target in lung cancer with wild-type EGFR - Jo, Ukhyun (Impact Journals LLC, 2014)
Oncogenic alterations of epidermal growth factor receptor (EGFR) signaling are frequently observed in lung cancer patients with worse differentiation and poor prognosis. However, the therapeutic efficacy of EGFR-tyrosine kinase inhibitors (TKIs) is currently limited in selected patients with EGFR mutations. Therefore, in this study, we investigated the potential molecular mechanism that contributes to cell viability and the response of gefitinib, one of the EGFR-TKIs, in lung cancer models with wide-type EGFR (wtEGFR). Interestingly, we found that EGF-induced EGFR endocytosis is existed differently between gefitinib-sensitive and -insensitive lung cancer cell lines. Suppressing EGFR endocytos decreased cell viability and increased apoptotic cell death in gefitinib-insensitive lung cancer with wtEGFR in vitro and in vivo. In addition, we found that Rab25 was differentially expressed in between gefitinib-sensitive and -insensitive lung cancer cells. Rab25 knockdown caused the changed EGFR endocytosis and reverted the gefitinib response in gefitinib-sensitive lung cancer with wtEGFR in vitro and in vivo. Taken together, our findings suggest a novel insight that EGFR endocytosis is a rational therapeutic target in lung cancer with wtEGFR, in which the combined efficacy with gefitinib is expected. Furthermore, we demonstrated that Rab25 plays an important role in EGFR endocytosis and gefitinib therapy.